Aplicação da Moringa oleifera na remoção de células de Microcystis aeruginosa e metabólitos por flotação por ar dissolvido e filtração rápida - Carvalho, Maiara Soares de (2015)
Nutrient inputs leads to more frequent algal blooms in water supply reservoir which causes operational problems in water treatment plants due to high density of cells, aside from complications induced by its capacity of production of cyanotoxins and taste and odour compounds. The present study had as purpose an evaluation of the applicability of Moringa oleifera Lam as a coagulant with and without polyaluminium chloride (PACl) in the removal of Microcystis aeruginosa cells, microcystins, 2-MIB and geosmin using dissolved air flotation and filtration, using granulated activated carbon (GAC). First, NaCl and CaCl2 salts were studied for extraction of the coagulant. Samples were obtained by the addition of humic acid and M. aeruginosa cells in synthetic water in order to obtain 25 NTU. Coagulant obtained with 1M CaCl2 showed a better performance for color, turbidity and cells removal, being indicated 50 mg L-1 dosage. CaCl2 would not extract better the active component of M. oleifera seeds, but participate on flocs formation. Based on this, PACl addition was evaluated and added in the ranges of 10 to 50% substitution of the saline coagulant. 70:30 and 60:40 proportions of M.oleifera:PACl were indicated in order to to remove turbidity, color and cells. Finally, the use of GAC as an intermediate layer in rapid sand filtration bed was evaluated as a function of microcystins, 2-mib and geosmine retention capacity. Cited proportions were followed by filtration, added of 2-MIB and geosmin 50 ng L-1 as well as 25 μg L-1 of microcystin-LR equivalent before tests. A 70:30 (M.oleifera:PACl) proportion followed by rapid sand filtration combined with GAC led to removal efficiencies above 95% for color, turbidity, M. aeruginosa cells, geosmin and microcystins, and 51 to 75% efficiencies for 2-MIB and dissolved organic carbon. Hence, M. oleifera usage as water coagulant with 30% of PACl can reduce costs for some countries, and the addition of a GAC layer on a sand filter can reduce cost and space in water treatment plants. This process is indicated as an alternative conventional treatment for the removal of cyanobacteria cells and metabolites, besides its capacity to maintain turbidity, color and microcystins below the stipulated levels for water consumption.